Perception, knowledge, and attitude on the impact of daytime nap on the risk of stroke among nonhealthcare undergraduate students - Chan, Chi Kuan (2022)
Daytime napping refers to a short duration of sleep during the day and it is a common practice in most part of the world. However, several evidence show that daytime nap may be one of the risk factors for brain stroke, but limited studies were done to evaluate the perception, knowledge, and attitude of the society. Therefore, the objective of this research was to assess the perception, knowledge, and attitude on the impact of daytime nap on the risk of stroke among non-healthcare undergraduate students using self-administered questionnaire. The sampling method used in the study was convenience sampling and a total of 400 participants were recruited for this study. A self-prepared questionnaire via an online platform with Cronbach’s alpha value of 0.834 was used and communication platforms such as WhatsApp and Microsoft Teams were used to collect data. Descriptive and inferential analysis were used to analyze the data collected including the usage of Spearman’s correlation test and Pearson Chi-Square test with IBM SPSS software statistics version 20. The total participants recruited were 400 participants but only 365 responses were included and processed due to 35 of the participants did not meet the inclusion criteria of this study. The average perception, knowledge, and attitude score of participants were 16.38±2.11, 6.90±1.08, and 11.49±1.36 respectively. No significant correlation was found between perception and attitude, knowledge and attitude and BMI and practice of daytime nap among non-healthcare undergraduate students in UTAR Sungai Long campus. In conclusion, the role of physiotherapists in the promotion of sleep health is undeniably crucial to raise the awareness and knowledge starting from the student community and gradually expanding to the general population by distributing pamphlets and organizing talks and workshops. This study concludes that the general population of non-healthcare undergraduate students in UTAR Sungai Long campus has an average perception, knowledge, and attitude towards the impact of daytime nap on the risk of brain stroke. However, the result is not generalizable to the overall population in Malaysia. Therefore, further studies can be done involving a wider population.